Ginseng extracts improve circadian clock gene expression and reduce inflammation directly and indirectly through gut microbiota and PI3K signaling pathway - Xue-Ying Zhang; Saeid Khakisahneh; Song-Yi Han; Eun-Ji Song; Young-Do Nam; Hojun Kim (npj Biofilms and Microbiomes, 2024)
Abstract Despite the potential benefits of herbal medicines for therapeutic application in preventing and treating various metabolic disorders, the mechanisms of action were understood incompletely. Ginseng (Panax ginseng), a commonly employed plant as a dietary supplement, has been reported to play its hot property in increasing body temperature and improving gut health. However, a comprehensive understanding of the mechanisms by which ginseng regulates body temperature and gut health is still incomplete. This paper illustrates that intermittent supplementation with ginseng extracts improved body temperature rhythm and suppressed inflammatory responses in peripheral metabolic organs of propylthiouracil (PTU)-induced hypothermic rats. These effects were associated with changes in gut hormone secretion and the microbiota profile. The in-vitro studies in ICE-6 cells indicate that ginseng extracts can not only act directly on the cell to regulate the genes related to circadian clock and inflammation, but also may function through the gut microbiota and their byproducts such as lipopolysaccharide. Furthermore, administration of PI3K inhibitor blocked ginseng or microbiota-induced gene expression related with circadian clock and inflammation in vitro. These findings demonstrate that the hot property of ginseng may be mediated by improving circadian clock and suppressing inflammation directly or indirectly through the gut microbiota and PI3K-AKT signaling pathways.